Relationship between ABO genotype and A antigen expression on platelets. Issue 8 (12th November 2012) - DeLelys, Michelle E.; Ochoa, Gorka; Cserti‐Gazdewich, Christine M.; Vietz, Christine; Preffer, Frederic I.; Dzik, Walter
<x xml:space="preserve">Abstract</x> Background Although platelets (PLTs) are known to express ABH antigens, the extent of expression is different on PLTs compared with red blood cells and the relationship between PLT ABH expression and genotype has not been thoroughly investigated. Study Design and Methods We measured blood group H and A antigens on PLTs from 100 normal volunteers using fluorescent‐conjugated reagents and flow cytometry. Individuals were also genotyped at the ABO locus using a commercially available genotyping system. Results Expression of A and H antigen varied widely on PLTs from different individuals. Among group A and AB persons, H antigen expression was significantly greater than A antigen (p < 0.0001). The ratio of H‐to‐A antigen expression varied more than 100‐fold in a predictable fashion according to genotype with values lowest in A1/A1 < A1/O < A2/A2 < A2/O. H and A antigen expression was unaffected by secretor status. The proportion of PLTs with high A expression also varied directly according to genotype. Conclusions Blood group A and H antigen expression on PLTs varies in a predictable fashion according to genotype. Flow cytometry and genotyping identify individuals who strongly express A antigens, a finding that may be relevant to clinical PLT transfusion across ABO barriers.